Interpolation method for live weight estimation based on age in Japanese quails - Senol Celik; Hakan Inci; Turgay Sengul; Bunyamin Sogut; Ahmet Yusuf Sengul; Mehmet Resit Taysi (Revista Brasileira de Zootecnia)
ABSTRACT The objective of this study was to demonstrate live weight estimation based on age by using Newton Interpolation method for male and female quails for seven weeks of fattening. A total of 138-day-old quail chicks were used in the study. The study demonstrated a 6th-degree polynomial interpolation for the function values obtained at seven equal intervals from 7 to 49 days. Live weight increase prediction was calculated for male and female quails between the 7th and 49th days using Newton Interpolation. Daily live weight increase for male and female quails based on observed live weights was determined. Female quails displayed more live weight increase after the 19th day compared with males. Average live weight increase in male quails was 3.81 g, and 4.63 g for females until the 49th day. The highest live weight increase was observed during the fourth week for all quails. Sum of squared errors and coefficient of determination (R2) for fit of the model were calculated and the F test was performed. F, sum of squared errors, and R2 obtained by Newton Interpolation for male quails and female quail were very large: 0 (approximately zero) and 0.999, respectively. The interpolation method is suitable for breeding studies.